KOMUNIKASI ANTAR PRIBADI GURU DI SLB SILIH ASIH DALAM PRESPEKTIF ISLAM - Nurjaman Nurjaman (Jurnal Komunikasi, 2025)
This study aims to analyze interpersonal communication of teachers at SLB Silih Asih Bandung from an Islamic perspective. The research method used is qualitative, while the collection techniques consist of in-depth interviews, participant observation, documentation studies, and literature studies. While data analysis uses an interactive model consisting of data condensation, data presentation, and drawing conclusions. The results of the study indicate that: 1) There are only two interaction patterns applied at SLB Silih Asih, namely the One-Way Pattern; 2) The Interpersonal Communication Method of Teachers with Children with Special Needs applied at SLBSIlih Asih C Bandung, uses five methods, including: Lecture Method, Independent Learning Method, Assignment Method, Demonstration Method, and Discussion Method; 3) The Interpersonal Communication Model of Teachers with Children with Special Needs at SLB Silih Asih C Bandung, uses the devito model, namely: Source-Receiver; 4) Islamic Religious Education is a reference in the Interpersonal Communication Process of Children with Special Needs at SLB Silih C Bandung using six qaulan phrases